Changes of Left Ventricular Mass Index Among End-Stage Renal Disease Patients After Renal Transplantation - Namazi, Mohammad Hassan; Alipour Parsa, Saeed; Hosseini, Banafshe; Saadat, Habibollah; Safi, Morteza; Motamedi, Mohammad Reza; Vakili, Hossein (Urology Journal, 2010)
Purpose: The aim of this study was to determine left ventricular (LV) mass index via echocardiography in end-stage renal disease patients (ESRD) before and after renal transplantation, and its association with one-year survival. Materials and Methods: Forty-seven patients with ESRD who were candidate for renal transplantation were evaluated with echocardiography before and 4 months after the operation. Left ventricular ejection fraction (EF), LV mass, and LV mass index were determined. All of the patients were followed up for 1 year.Results: Mean LVEF was 51.6% which increased to 53.7% after renal transplantation (P = .001). Mean LV mass was 209 gr before the operation which decreased to 189 gr after the operation (P = .001). Mean LV mass index before the operation was 120 gr/m2 which decreased to 110 gr/m2 following the operation (P = .002). All of the patients survived during 1-year follow-up, and no death was reported.Conclusion: Renal transplantation had beneficial effects in terms of LV function in young patients with ESRD.